A Psycholinguistic Analysis of Translation Processes - Lörscher, Wolfgang (Meta)

(untitled) (Les Presses de l'Université de Montréal, 1996)
AbstractThis article, outlines a project in which translation processes are investigated empirically on the basis of a corpus of translations. After a description of the methodology used, a model for the analysis of translation processes is presented followed by a brief comparison of professional and non-professional translation processes. In the concluding section, considerations are made as regards implications of translation process analysis for translation teaching.